Rapid Cooling and Increased Storminess Triggered by Freshwater in the North Atlantic. Issue 14 (24th July 2020) - Oltmanns, M.; Karstensen, J.; Moore, G. W. K.; Josey, S. A.
Abstract: Recent winters have been unique due to the rapid and extreme cooling of the subpolar North Atlantic. Here, we present a novel view on its causes and consequences. Combining in‐situ observations with remote sensing and atmospheric reanalysis data, we show that increased freshening of the subpolar region gives rise to a faster surface cooling in fall and winter. Large freshwater events, in particular, result in pronounced cold anomalies with sharp temperature gradients that promote an enhanced storminess. The storms reinforce the cooling by driving stronger heat losses and modulating the surface flow. Consistent with this mechanism, past freshwater events have been followed by cold anomalies in winter of approximately −2°C and increases in the North Atlantic Oscillation index of up to ∼0.6 within 3 years. We expect that future freshwater discharges into the North Atlantic will amplify the cold anomaly and trigger an enhanced wintertime storminess with far‐reaching climatic implications. Plain Language Summary: Recent winters have been unique due to a rapid and extreme cooling of the subpolar North Atlantic. Combining ocean and atmospheric data, we show that increased freshwater in this region leads to shallower surface layers that adjust faster to the lower air temperature in fall and winter. The faster surface cooling increases the south‐north temperature gradient, which promotes the development of storms. The storms, in turn, reinforce the cooling by modulating the surface flow. Accordingly, past freshwater events have been followed by an extremely cold ocean surface in the subpolar North Atlantic in winter and major changes in large‐scale weather patterns. We expect that future freshwater discharges from Greenland and the Arctic will amplify the cooling and trigger an enhanced wintertime storminess with far‐reaching implications for the climate. Key Points: Large freshwater events result in distinct cold anomalies with sharp temperature gradients in the subpolar North Atlantic in winter A strong, freshwater‐induced cold anomaly promotes an enhanced storminess, which reinforces the anomaly by modulating the surface flow Consistent with this mechanism, large freshwater events in the past have preceded positive North Atlantic Oscillation periods in winter